Analisis Kebutuhan Model Pembelajaran Kooperatif pada Pembelajaran Matematika - Ningrum, Izza Eka (Lembaga Yasin AlSys, 2022)
The learning model used so far is still less effective, which is one of the reasons for the low learning outcomes of mathematics in students. This study aims to analyze the needs of the learning model on students' mathematics learning outcomes. This research is a qualitative research with qualitative description research type. The research subjects were students of class VIII Junior High School. The research data were collected by means of interviews and observations. The results of this study indicate that: (1) the teacher has not been precise in choosing the learning model (2) students have not been actively involved in learning in class (3) students still do not dare to ask if they have difficulties so that the learning process is not effective (4) students in the teaching and learning process only listen, take notes, do what the teacher tells them to do and do not dare to ask for difficulties in understanding the material. Therefore, it is necessary to decide the right learning model in the teaching and learning process of mathematics in order to make it easier for students to accept the material presented.